The effect of career development and work motivation on employee job satisfaction at PT. SOURCE OF ALFARIA TRIJAYA, JAMBI CITY - kurniawan, Doni; Anwar Us, Kasful (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2021)
Abstract This study aims to explain whether the variables of career development and motivation work has a significant effect on employee job satisfaction at PT. Source Alfaria Trijaya and knowing which variable is more dominant between the two. From the results of the data analyzed by using qualitative methods and quantitative methods, found results that show that together or simultaneously, the two factors that In this study, it has a positive effect on the independent variable, namely job satisfaction. employee with the result Y= ,???????????? + ,???????????? + , + . Then when in review From the results of the coefficient of determination, it is found that the magnitude of the contribution of the two variables is This impact on performance satisfaction reached 59.9% and the rest was influenced by other factors, which Thus, it is concluded that the studied variable has an effect on job satisfaction employees.